Equity premium and monetary policy in a model with limited asset market participation - Roman Horváth; Lorant Kaszab; Ales Marsal (Magyar Nemzeti Bank, 2020)
We develop a dynamic stochastic general equilibrium model calibrated to US data to examine how monetary policy shocks affect income inequality and the equity premium. The model features Ricardian and non-Ricardian households and shows that a monetary policy tightening causes an endogenous redistribution of income from non-Ricardians to Ricardians. Ricardians' consumption comoves more strongly with asset returns, giving rise to high equity premia. We extend our model with several frictions and estimate it with generalized method of moments using US macroeconomic and financial data from 1960-2007. We find that the estimated model jointly matches the bond and equity premia. We complement our theoretical model with vector autoregression estimations and show that a tightening of US monetary policy increases equity premia.
Keywords: E32; E44; G12; 330; Limited Asset Market Participation; Monetary Policy; DSGE; Equity Premium